2006
DOI: 10.1021/jp061960w
|View full text |Cite
|
Sign up to set email alerts
|

EPR and DFT Studies of the Structure of Phosphinyl Radicals Complexed by a Pentacarbonyl Transition Metal

Abstract: Paramagnetic complexes M(CO) 5 P(C 6 H 5 ) 2 , with M ) Cr, Mo, W, have been trapped in irradiated crystals of M(CO) 5 P(C 6 H 5 ) 3 (M ) Cr, Mo, W) and M(CO) 5 PH(C 6 H 5 ) 2 (M ) Cr, W) and studied by EPR. The radiolytic scission of a P-C or a P-H bond, responsible for the formation of M(CO) 5 P(C 6 H 5 ) 2 , is consistent with both the number of EPR sites and the crystal structures. The g and 31 P hyperfine tensors measured for M(CO) 5 P-(C 6 H 5 ) 2 present some of the characteristics expected for the diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…It is worthwhile mentioning that irradiation of crystals of Mo(CO) 5 PPh 3 leads to the detection of the main species expected from common mechanisms in radiation chemistry: (1) formation of the radical cation, which is not stable above 100 K, (2) formation of the radical anion, which results from the capture of a thermalized electron by a surrounding neutral molecule; this anion could be detected even after annealing at 300 K [36], (3) formation at room temperature of a radical species due to the homolytic scission of an organic bond; in this case (CO) 5 Mo-PPh 2 [17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthwhile mentioning that irradiation of crystals of Mo(CO) 5 PPh 3 leads to the detection of the main species expected from common mechanisms in radiation chemistry: (1) formation of the radical cation, which is not stable above 100 K, (2) formation of the radical anion, which results from the capture of a thermalized electron by a surrounding neutral molecule; this anion could be detected even after annealing at 300 K [36], (3) formation at room temperature of a radical species due to the homolytic scission of an organic bond; in this case (CO) 5 Mo-PPh 2 [17]. …”
Section: Discussionmentioning
confidence: 99%
“…[16]. As previously explained, the crystal was glued on a small brass cube with Y//c* and a*//ÀX (the crystallographic axes correspond to the reduced cell) [17]; then it was immersed in liquid nitrogen and exposed at 77 K for 2 h to the radiation of a X-rays tube (PW Phillips tube, tungsten anticathode, 30 kV, 30 mA). Any increase in the temperature of the sample was carefully avoided, the crystal was transferred to a finger dewar, and positioned in the EPR cavity of a Bruker 300 spectrometer (X-band).…”
Section: Methodsmentioning
confidence: 99%
“…It is generally admitted that these intermediates can be divided into two main classes [3,4]: (i) organic radicals coordinated to a transition metal complex [5], (ii) paramagnetic complexes with a considerable localisation of the unpaired electron on the metal. We have recently shown that (CO) 5 M-Å PR 2 , a species of the former class, can be formed from M(CO) 5 PR 3 (with M = Cr, Mo, W) [6]. Here, we show that, by changing the experimental conditions, the same precursor can lead to a metal-centred radical anion [M(CO) 4 PR 3 ] ÅÀ .…”
Section: Introductionmentioning
confidence: 61%
“…[6], at room temperature, single crystals of W(CO) 5 PPh 3 , Mo(CO) 5 PPh 3 and Cr(CO) 5 PPh 3 previously irradiated at 300 K, showed only the signals due to the trapping of the phosphinyl radical linked to the pentacarbonylmetal: (CO) 5 M-Å PPh 2 . However, these spectra drastically changed when the crystals, previously irradiated at 300 K, were studied at 77 K. Probably due to saturation, the lines assigned to (CO) 5 M-Å PPh 2 considerably decreased in intensity, while new signals clearly appeared on the spectra; moreover, the above described signals A and B, generated by irradiation at 77 K, were not detected.…”
Section: Epr Spectramentioning
confidence: 96%
“…6). [12] Stimulated by the recent developments in molecular electronics, the EPR group simultaneously intensified its efforts in three directions: i) The design of molecular systems capable of accepting or losing a single electron and delocalizing the resultant unpaired spin over a large part of the molecule. Most of these new compounds were based on phosphorus compounds with a low coordination number ( Fig.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%